Collaboration among Faculty Members and Community Partners: Increasing the Quality of Online Library and Information Science Graduate Programs through Academic Service-Learning. - Angel, Christine M. (Journal of Library & Information Services in Distance Learning)
Finding innovative ways to deliver effective classroom instruction resulting in demonstration of student proficiency of the eight American Library Association core competencies within the online learning environment is challenging. While the use of technology is very important in the delivery of course content, focusing on the pedagogy of teaching online classes is paramount when constructing a comprehensive online teaching curriculum. This article describes how one professor integrates both theory and experience together within the online learning environment as a means for students to demonstrate proficiency of course concepts. Academic Service-Learning, construction of real-world collaborative projects and lessons learned are discussed.